Lactic acidosis and hypoglycemia as markers of disease progression of multiple myeloma: A case report. Issue 3 (5th May 2021) - Ziegler, Caroline; Volkov, Lev; Marnai, Rémy; Courte, Guilhem; Cravoisy, Aurélie; Conrad, Marie; Nace, Lionel; Melone, Agnès; Perrot, Aurore; Gibot, Sébastien
Abstract: Case report : A 64‐year‐old man was hospitalized in the intensive care unit with pneumonia, lactic acidosis, and hypoglycemia. Investigations revealed a kappa light chain multiple myeloma. The patient underwent chemotherapy by bortezomib, lenalidomide, and dexamethasone. Serum lactate level and glycemia normalized. Evaluation at day 28 showed a disease progression. Lenalidomide was switched for daratumumab, bortezomib, and dexamethasone. In front of the inefficiency of the chemotherapy, the patient underwent third‐line chemotherapy by melphalan. There was a correlation between the evolution of the myeloma, serum lactate level, and hypoglycemia, with a normalization after chemotherapy, and a rise at myeloma's relapse. Daratumumab was continued as a maintenance treatment. The patient died 4 months and 10 days after his first hospital admission. Discussion : Our case is consistent with a type B tumor‐associated aerobic glycolytic lactic acidosis, called the Warburg effect. It is well described in association with other hematologic malignancies, but rarely in association with myeloma. All reported cases of myeloma with type B lactic acidosis died within 1 year. Conclusion : When associated with multiple myeloma, tumor‐associated aerobic glycolytic lactic acidosis is correlated with the disease progression and has a very high mortality rate. Significance Statement : Aerobic glycolytic lactic acidosis also known as the Warburg effect can be encountered in multiple myeloma, resulting of a metabolic shift to increased glycolysis operating in malignant cells. Together with hypoglycemia, it is well correlated with the disease progression and has a very poor outcome.